All is not lost that is delayed: overconfidence and investment outcomes - André Betzer; Inga van den Bongard; Felix Schweder; Erik Theissen; Christine Volkmann (Review of Managerial Science, 2022)
We use a unique panel data set of private German firms to analyze the relation between managerial overconfidence and investment policy in small and medium-sized firms. We find that overconfident managers invest more, and that this relation is driven by expansion investments. When considering the outcome of investment projects, we find that projects initiated by overconfident managers are less likely to be completed as planned. When we differentiate between three types of non-completion (downsizing, delaying, and abandoning), we find that overconfident managers are more likely to delay, rather than to abandon or downsize a project.
Keywords: G31; G32; O16; 650; Overconfidence; Small and medium-sized enterprises; Corporate investment; Private companies